PENGARUH KOMITE AUDIT, AUDIT EKSTERNAL DAN DEWAN KOMISARIS TERHADAP MANAJEMEN LABA - Rosana Velly Hermitasari; Agus Purwanto (Diponegoro Journal of Accounting, 2016)
Audit committee, External Audit, and Board of Commissioner have a very important role to oversee the financial reporting process and monitor the propensity of a company managers to manipulate earnings. This study uses secondary data from annual reports and financial statements on non-financial companies listed on the Indonesia Stock Exchange in 2014. The sampling method used is purposive sampling. The total number of samples in this study were 93 data, but after going through the stages of data processing, there are 1 of data outliers that should be excluded from the sample. Thus, the total number of eligible final sample was observed that 92 data. Variable earnings management, activeness of the audit committee, the expertise finance of audit committee , external audit , the expertise finance of commisioner, indpendence of commisioner and activeness of commisioner actionanalyzed by Ordinary Least Square regression. Activeness of the audit committee and the expertise finance of commisioner significantly do not impact of earnings management, while the external audit significantly impact the earnings management. However, the expertise finance of audit committee, the board of activeness of commisioner and the indpendence of commisioner independence have not significant effect on earnings management.